2018
DOI: 10.1016/j.celrep.2018.07.103
|View full text |Cite
|
Sign up to set email alerts
|

A Nuclear Export Block Triggers the Decay of Newly Synthesized Polyadenylated RNA

Abstract: SummaryGenomes are promiscuously transcribed, necessitating mechanisms that facilitate the sorting of RNA for function or destruction. The polyA (pA) tail is one such distinguishing feature, which in the Saccharomyces cerevisiae nucleus is bound by the Nab2p protein, yielding transcript protection. As Nab2p also contacts the main nuclear export factor Mex67p, we asked whether transport kinetics contributes to RNA sorting. Indeed, 3′ end sequencing of newly transcribed pA+ RNAs demonstrates that nuclear depleti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
44
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(56 citation statements)
references
References 59 publications
11
44
0
Order By: Relevance
“…We speculate that an abundant number of introns might increase RNA nuclear residence time and therefore require NCBP3 to fend off nuclear decay activities (as exemplified by its competition with ZC3H18), while providing additional export capacity. As shown previously in both yeast and human cells, efficient nuclear export is required to evade nuclear decay by the RNA exosome (29,64,65). Loss of NCBP3 might therefore de-stabilize these multiexonic transcripts dually due to their slowed nuclear export and enhanced turnover (Fig.…”
Section: Discussionsupporting
confidence: 63%
“…We speculate that an abundant number of introns might increase RNA nuclear residence time and therefore require NCBP3 to fend off nuclear decay activities (as exemplified by its competition with ZC3H18), while providing additional export capacity. As shown previously in both yeast and human cells, efficient nuclear export is required to evade nuclear decay by the RNA exosome (29,64,65). Loss of NCBP3 might therefore de-stabilize these multiexonic transcripts dually due to their slowed nuclear export and enhanced turnover (Fig.…”
Section: Discussionsupporting
confidence: 63%
“…Critically, in the absence of nuclear Nab2, nuclear mRNA is rapidly degraded by the RNA exosome . Moreover, if nuclear export of mature mRNPs is blocked, newly synthesized mRNA transcripts are quickly degraded and this has been proposed to be because of the reduced availability of Nab2, which is unavailable because it is bound to the older previously generated transcripts …”
Section: Scnab2 Regulation Of Poly(a) Tail Lengthmentioning
confidence: 99%
“…56 Moreover, if nuclear export of mature mRNPs is blocked, newly synthesized mRNA transcripts are quickly degraded and this has been proposed to be because of the reduced availability of Nab2, which is unavailable because it is bound to the older previously generated transcripts. 57 Overall, extensive analyses of ScNab2 Zn finger variants has indicated that the ScNab2 ZnF567 interaction with polyadenosine RNA plays a central role in the regulation of poly(A) tail length and mRNA compaction in S. cerevisiae. In this context, the observation that the loss of DmNab2 in Drosophila and ZC3H14 in mice and humans results in longer poly(A) tails 12,13,55 suggests that DmNab2 ZnF123 and ZC3H14 ZnF123, which are most similar to ScNab2 ZnF567 [ Fig.…”
Section: Scnab2 Regulation Of Poly(a) Tail Lengthmentioning
confidence: 99%
“…Inactivation of Mex67 leads to nuclear accumulation of mRNA ( Segref et al, 1997 ; Santos-Rosa et al, 1998 ). In addition, in the absence of Mex67, poly-A + RNA appears to be extremely unstable, which was attributed to untimely RNA decay due to the export block ( Tudek et al, 2018 ). Notably, Mex67 is also somehow implicated in the cytoplasmic export of Xpo1-transported cargoes, such as snRNA, rRNA, and tRNA, raising a question of why these RNA species require two export receptors ( Yao et al, 2007 ; Faza et al, 2012 ; Chatterjee et al, 2017 ; Becker et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%